1998
DOI: 10.1108/09564239810199932
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment, attribution and apologising as dimensions of service recovery

Abstract: IntroductionBusiness managers frequently refer to the competitive nature of the markets they serve. The increasing globalisation of business is often cited as a major contributing factor. Managers of service firms in countries which are signatories of the Uruguay Round of the GATT agreement, in particular, may soon feel the uncomfortable heat of increased competition as protective trade barriers are systematically removed. This development is likely to re-establish customer retention as a strategic marketing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
2
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(164 citation statements)
references
References 55 publications
(36 reference statements)
2
147
2
13
Order By: Relevance
“…al. [25], as the correlations are based on a substantially larger corpus in comparison to other similar work [40] [27] [29], and also because their effectiveness of deriving personality traits has been independently validated and used by other researchers [36] [28].…”
Section: Robustness Test: Controlling For the Personality Of The Custmentioning
confidence: 99%
See 2 more Smart Citations
“…al. [25], as the correlations are based on a substantially larger corpus in comparison to other similar work [40] [27] [29], and also because their effectiveness of deriving personality traits has been independently validated and used by other researchers [36] [28].…”
Section: Robustness Test: Controlling For the Personality Of The Custmentioning
confidence: 99%
“…It might not matter how friendly, pleasant, or attentive an employee is to a customer if the employee is not able to solve the problem or to be seen as trying to help, as the customer will just become more dissatisfied [35]. Prior studies find that full empowerment to solve the complaint immediately has a significant impact on satisfaction with the recovery [36]. However, it is questionable whether the brands providing customer service on social media today have the ability and authority to fully rectify customer complaints.…”
Section: H2: a Complaining Customer Is More Likely To Feel Better Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Empowerment allows employees to deal with customers efficiently and it is argued that empowerment is vital for service companies that require face-to-face contact between customers and frontline employees (Baron and Harris, 2003;Boshoff and Leong, 1998).…”
Section: Contribution Of Study and Managerial Implicationsmentioning
confidence: 99%
“…However, the findings of these studies are mixed and thus, inconclusive. Similarly, many studies have reported significant effect of customer complaints (e.g., Awwad, 2011;Fornell, Johnson, Anderson, Cha, & Bryant, 1996;Zeithaml, Berry, & Parasuraman, 1996) and service recovery (e.g., Boshoff, 1999;Boshoff & Leong, 1998;Dewitt, Nguyen, & Marshall, 2007;Kitapci & Dortyol, 2009) on customer loyalty. Yet, service recovery application is not quite understood in the banking sector (Kumunda & Osarenkhoe, 2012).…”
Section: Introductionmentioning
confidence: 99%